Origin and history of trace elements accumulation in recent Mediterranean sediments under heavy human impact. A case study of the Boka Kotorska Bay (Southeast Adriatic Sea). (June 2022) - Mikac, Nevenka; Sondi, Ivan; Vdović, Neda; Pikelj, Kristina; Ivanić, Maja; Lučić, Mavro; Bačić, Niko; Turk, Martina Furdek; Škapin, D. Srečo; Krivokapić, Slađana
Abstract: The history of metal pollution in the semi-enclosed and human-influenced marine system of the Boka Kotorska Bay (Southern Adriatic) was studied considering geological composition of the surrounding catchment, the sedimentation rate and the mineralogical and early diagenetic processes in the recent sediments. The determination of background concentrations of metals, undertaken for the first time in this environment, proved to be particularly important for Ni and Cr, which are naturally enriched in the sediments of the southern Adriatic. The results showed widespread moderate contamination with Pb and Sn since the 1970s, while the upper layers of sediments near shipyards, marinas and urban areas were more contaminated with Sn, Cu, Pb, Zn, Cd, As, Sb and Mo. The transport of material through the narrow straits separating different parts of Boka Kotorska Bay resulted in a different geochemical composition of the smaller bays and a limited distribution of contaminated sediments from local sources. Graphical abstract: Unlabelled Image Highlights: The history of metal pollution in Boka Kotorska Bay was determined in sediment cores. Verified local metal backgrounds are required to assess the extent and history of pollution. Metals have different vertical profiles depending on the pollution source. Shipyards are the main sources of metal pollution of coastal sediments. Mineral and geochemical composition of sediments varies due to geological setting.